Impact of poaching on the marketability of safari lodges in the Eastern Cape - Loader, Rory James (Rhodes University, Faculty of Commerce, Rhodes Business School, 2015)
This research is presented in three sections. Section 1 presents the research report in an academic paper format. Section 2 provides a comprehensive literature review and Section 3 describes the research methodology and methods employed during the research. The tourism industry is the fastest growing sector within the South African Economy, with over 2.6 million foreign tourists visiting South Africa each year. Wildlife, landscapes and scenery are cited as the primary attractions for visiting the country, with over 45 percent of tourists visiting at least one wildlife or nature reserve during their stay in South Africa (Kerley et al., 2011:2). Sixty percent of those tourists travelled for leisure purposes, with 643,883 of the tourists utilising safari lodge accommodation during their visit (Ruggles-Brise, 2013). The Eastern Cape achieved 3.1 percent; of those tourist arrivals, with a bed-night contribution of 734,339, compared to the 16.8 percent (1.9million) and 10.5 percent (1.07million) for Mpumalanga and Limpopo provinces respectively (Ruggles-Brise, 2013). The Eastern Cape lodges represent less than half the bed-nights achieved by Mpumalanga and Limpopo lodges. Due to the number of possible bed-nights available to lodges in the Eastern Cape, it is increasingly important for individual lodges to provide a unique experience, in order to be competitive in attracting guests (Saayman, 2013:81). This was used form part of the foundation to this research in determining the marketability of three lodges in the Eastern Cape, which was derived from the attractiveness of the lodges, determined by guests visiting the lodges. This research follows on from four previous surveys commissioned by INDALO, the Eastern Cape Private Nature Reserve Association in 2004 Sims-Castley et al. 2004), 2006 (Langholz et al., 2006), 2008 (Snowball et al., 2008) and 2011 (Kerley et al., 2011). Part of the research was to identify the main attractions of the reserves. These previous surveys provided a foundation for this research to follow on investigating guest motivations for visiting the three sample lodges and to determine visitor perception of poaching and whether it would impact their motivations for visiting the reserve. In order to address the goals of the research qualitative data was gathered during survey interviews conducted at the three sampled reserves. Seventy five (75) guests were interviewed, equally over the three reserves. Quantitative data was also gathered during the interview surveys, utilising Likert scale questions, prompting guests to choose their top attractions, from which basic descriptive statistics were used to analyse the data being able to determine possible trends amongst respondents and lodges. Results verified guest motivations from the previous surveys, confirming that game viewing, especially the "Big 5" remained the most important attraction for visitors to the reserves while the availability of natural scenery and landscape, high end accommodation and service, the proximity to the garden route and being located in a malaria free area were also see as attractive attributes of the lodges as per the previous surveys. Where the gap in the research was indicated based on guests perception of poaching and whether it would impact their motivations for visit these lodges, impacting that lodges marketability (attractiveness). Results indicated that if they were unable to view the iconic 'Big Five' at the reserve due to the extent of poaching. Respondents indicated that the impact would likely and very likely impact their decision to choose the reserves over another reserve that could. Indicating the potential impact that poaching would have on lodges if they were to lose their iconic species which would spell the loss in attractiveness and therefore marketability.
Keywords: Safari lodges -- South Africa -- Eastern Cape -- Marketing; Poaching -- South Africa -- Eastern Cape; Ecotourism -- South Africa -- Eastern Cape; Wildlife crimes -- South Africa -- Eastern Cape